Association of periodontitis with tinnitus: A population‐based cohort study in Taiwan. (17th June 2022) - Su, Suzanne Ying‐Shan; Chien, Wu‐Chien; Chung, Chi‐Hsiang; Su, Wan‐Fu; Fu, Earl
Abstract: Aim: Tinnitus, ringing in the ears, is speculated to be driven by inflammation. This study examined whether periodontitis is a risk factor for tinnitus using Taiwan's National Health Insurance Research Database. Materials and Methods: Among the 79, 456 patients who visited for dental concerns, 11, 055 patients who were diagnosed with periodontitis and underwent periodontal treatment between 2000 and 2015 were enrolled in Group 1. After matching for sex, age, and index year, 11, 055 patients with periodontitis who received no treatment were enrolled in Group 2. Similarly, 11, 055 participants without periodontitis were included as controls. Results: At the end of the follow‐up, 412 and 404 participants in the two periodontitis groups and 321 participants in the control group had tinnitus. Cumulative risk for tinnitus in Group 1 or 2 was significantly greater than in the control group. More periodontitis patients than controls developed tinnitus (adjusted hazard ratios were 1.71 (95% confidence interval [CI]: 1.49–1.97, p  < .001) and 1.64 (95% CI: 1.37–1.86, p  < .001) in Groups 1 and 2, respectively). The risks were not significantly different between Groups 1 and 2. Similar findings were obtained after excluding data for the first 1 or 5 years. Conclusions: The study findings indicate that periodontitis is associated with tinnitus.